Quality by design approach for simultaneous determination of original active pharmaceutical ingredient quinabut and its impurities by using HPLC. Message 1 - Golembiovska, O.; Voskoboynik, O.; Berest, G.; Kovalenko, S.; Logoyda, L.; Берест, Галина Григорівна; Коваленко, Сергій Іванович (My University, 2021)
The aim of study was to develop and validate a simple, highly robust (quality by design (QbD) approach), precise and accurate method using high performance liquid chromatography for the simultaneous determination of original active pharmaceutical ingredient Quinabut and its impurities. Materials and methods. Experiments were performed on a Shimadzu LC-20 Prominence HPLC separation module, equipped with a quaternary gradient pump, temperature controlled column heater, sampler manager and diode array detector and LC-20 Chemstation for data analysis (Shimadzu Corporation, Japan). Same software was used for data acquisition and processing of results. X-Terra RP18 (4.6×150 mm, 5 μm) analytical chromatographic column provided by Waters Corporation (Milford, MA) was used for all optimization experiments. Mobile phase A: acetonitrile R. Mobile phase B: 0.025 M phosphate buffer solution. Samples were chromatographed in gradient mode. Flow rate of the mobile phase: 0.7 mL/min. Column temperature: 40 °С. Detection: at 233 nm wavelength. Injection volume: 50 μl. Results. Screening of the influence of four chromatographic factors on different chromatographic responses was performed as the initial step of analytical method optimization. A randomized fractional factorial experimental design (24–1) of resolution IV with central point was used. Buffer pH, amount of acetonitrile in mobile phase A, the amount of phosphate buffer solution in mobile phase B and column temperature were selected as factors of interest, and were used to generate the fractional factorial experimental design. Linearity was established in the range of LOQ level to 0.2% having regression coefficients 0.9977. Calibration curve – y = 0.0132 + 0.9902. Since Δt for the content of quinabut is less than max δ, the technique is stable over time. The possibility of contamination of the sample by decomposition products by keeping it under stressful conditions (irradiation of the substance solution with UV light (UV irradiation with mercury lamp light); acid hydrolysis with 0.1 M hydrochloric acid solution; oxidative decomposition) was investigated. As a result of the irradiation with UV light, the impurity peaks for about 8.74 min (impurity C) and 12.68 min (impurity B) are additionally revealed. Their content exceeds the limits of normalization and is 0.6% and 3.7%, respectively. Therefore, the powder of the substance and its solutions should be stored away from direct sunlight. The column temperature and the speed of the mobile phase within ± 10% did not significantly affect the test results. The results were found to be within the assay variability limits during the entire process.Conclusion. 1) The optimization of a new analytical method capable of simultaneous determination of quinabut assay and its impurities drug products was performed with a single fractional factorial experimental design. Only 11 experiments were needed for the optimization, while at least 16 experiments would be needed to cover the same analytical method operational region of the first optimization step with a traditional one factor at time (OFAT) approach. 2) HPLC method was developed and validated for the simultaneous detection and quantitation of quinabut and its impurities. 3) The final analytical method optimized with QbD approach was validated according to ICHQ2R1 guideline. The method proved to be sensitive, selective, precise, linear, accurate and stability-indicating. 4) The method was successfully applied to the analysis of demonstrating acceptable precision and adequate sensitivity for the detection and quantitation of quinabut and its impurities. So it may be reasonable to claim that the method can be extended to the analysis of drug formulations and stability samples as well. This optimization reflects in saving of time and resources since one stability study includes hundreds of samples tested during the product’s shelf life.
Keywords: Quality by Design; HPLC; Quinabut; Impurities; Validation